Review of Israel's action and response during the COVID-19 pandemic and tabletop exercise for the evaluation of readiness and resilience-lessons learned 2020-2021 - Khitam Muhsen; Khitam Muhsen; Dani Cohen; Dani Cohen; Aharona Glatman-Freedman; Aharona Glatman-Freedman; Sari Husseini; Saritte Perlman; Carrie McNeil (Frontiers Media S.A., 2024)
BackgroundReevaluating response plans is essential to ensuring consistent readiness and resilience to the COVID-19 pandemic. The "During Action Review" and Tabletop (DART) methodology provides a retrospective and prospective assessment to inform the adaptive response. Israel introduced COVID-19 vaccinations in December 2020 and was the first country to implement booster vaccination to address waning immunity and surges caused by new variants. We assessed Israel's readiness and resilience related to COVID-19 response while capturing the pre-vaccination and vaccination periods.MethodsA DART analysis was conducted between December 2020 and August 2021 among experts involved in the management of the COVID-19 pandemic in Israel. During the retrospective stage, a role-based questionnaire and discussions were undertaken in a participant-led review of the response, focusing on epidemiology and surveillance, risk communication, and vaccines. The prospective stage included tabletop exercises to evaluate short to long-term simulated scenarios.ResultsParticipants emphasized the pivotal role of Israel globally by sharing experiences with the pandemic, and vaccination. Perceived strengths included multi-sectoral collaboration between the Ministry of Health, healthcare providers, academia, military, and others, stretching capacities, expanding laboratory workload, and establishing/maintaining surveillance. The vaccine prioritization plan and strong infrastructure, including computerized databases, enabled real-life assessment of vaccine uptake and impact. Challenges included the need to change case definitions early on and insufficient staffing. Quarantine of patients and contacts was particularly challenging among underprivileged communities. Risk communication approaches need to focus more on creating norms in behavior. Trust issues and limited cooperation were noted, especially among ethnic and religious minorities. To ensure readiness and resiliency, participants recommended establishing a nationally deployed system for bringing in and acting upon feedback from the field, especially concerning risk communication and vaccines.ConclusionOur study appraised strengths and weaknesses of the COVID-19 pandemic response in Israel and led to concrete recommendations for adjusting responses and future similar events. An efficient response comprised multi-sectoral collaboration, policy design, infrastructure, care delivery, and mitigation measures, including vaccines, while risk communication, trust issues, and limited cooperation with minority groups were perceived as areas for action and intervention.